(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Two new topical immunosuppressive treatments, pimecrolimus and tacrolimus, were developed to provide alternatives to topical corticosteroids without the associated adverse events. They work by inhibiting calcineurin in the skin, which regulates the activity of several transcription factors that control cell division and trigger the early stages of T cell activation. Topical tacrolimus inhibits experimentally induced allergic contact dermatitis, and preliminary studies have suggested that the drug is effective in the treatment of atopic dermatitis.